Factors that influence customer and family satisfaction with palliative care: scoping review - Pinto,Igor (2022)
Abstract Introduction The assessment of satisfaction with palliative care (PC) from the perspective of its primary beneficiaries is essential and is consolidated with the ethical duty of health professionals to provide the best care. Objective To synthesize the scientific evidence on the factors that influence the assessment of customer satisfaction with PC and identify the instruments used for its assessment. Methods Review according to the Joanna Briggs Institute method for carrying out a scoping review. The search was carried out in Scopus, CINAHL Complete and Web of Science databases, and in OpenGrey, and Dart-Europe in July 2021. The selection was carried out by two independent researchers and the data were grouped into themes according to their contents. Results Forty studies were included. From the analysis carried out, researchers concluded that the factors that influence the assessment of satisfaction were grouped into five themes: Availability of Care, Physical Care, Psychosocial Care, Communication of Information and Care for the Patient in Imminent Death. Conclusion FAMCARE is the most widely used measurement instrument to assess customer satisfaction with PC. Knowledge of influencing factors allows both organizations and professionals to promote better personalization of care, to ensure safety and quality, and to adjust to the expectations of clients and caregivers.